Concomitant Thoracic Spinal Hemangioma and Dural Arteriovenous Fistula: Case Report and Technical Note - Stefano Vecchioni; Alessio Iacoangeli; Elia Giacomo Galli; Massimo Vissani; Alessandra Marini; Roberta Benigni; Michele Luzi; Roberto Trignani (Reports)
Background and Clinical Significance: The coexistence of spinal hemangiomas and dural arteriovenous fistula (SDAVF) is uncommon. Unclear imaging and progressive neurological impairment require early surgical management. Case Presentation: A 76-year-old woman presented with progressive thoracolumbar pain and worsening bladder dysfunction. Magnetic resonance imaging (MRI) of the thoracic spine revealed a round-shape expansive lesion at T11 with spinal cord edema and homogeneous contrast enhancement. Despite a chronic presentation, the subacute progression of bladder dysfunction and spinal cord edema warranted timely intervention. Intraoperatively, a vascular malformation resembling a dural arteriovenous fistula (SDAVF), unrecognized at pre-operative imaging, was found in association, and histological examination confirmed the diagnosis of hemangioma. The mechanism of coexistence remains unclear, although venous hypertension due to fistula could induce vascular malformations. Conclusions: This case emphasizes the importance of thorough imaging, timely intervention and intraoperative assessment in patients presenting with a suspicion of spinal hemangioma; it may also provide awareness of potentially associated concurrent lesions such as SDAVFs, unrecognized at pre-operative imaging, and technical insights during surgery.